2019
DOI: 10.3389/fnins.2019.01153
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Choir Singing Supports Speech-in-Noise Perception and Neural Pitch Strength in Older Adults With Age-Related Hearing Loss

Abstract: Prior studies have demonstrated musicianship enhancements of various aspects of auditory and cognitive processing in older adults, but musical training has rarely been examined as an intervention for mitigating age-related declines in these abilities. The current study investigates whether 10 weeks of choir participation can improve aspects of auditory processing in older adults, particularly speech-in-noise (SIN) perception. A choir-singing group and an age- and audiometrically-matched do-nothing control grou… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
71
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(84 citation statements)
references
References 163 publications
(224 reference statements)
9
71
1
3
Order By: Relevance
“…Groups did not differ in pre- to post-training improvements of sentence-in-noise tasks during or outside EEG recording. This is in contrast to experimental evidence demonstrating benefits in behavioral speech-in-noise abilities after 10 weeks of choir training [ 68 ] and 6 months of piano training [ 69 ], both in older adults. However, with the same group of participants, [ 108 ] did not observe behavioral differences in an in-scanner task of hearing in noise.…”
Section: Discussioncontrasting
confidence: 94%
See 2 more Smart Citations
“…Groups did not differ in pre- to post-training improvements of sentence-in-noise tasks during or outside EEG recording. This is in contrast to experimental evidence demonstrating benefits in behavioral speech-in-noise abilities after 10 weeks of choir training [ 68 ] and 6 months of piano training [ 69 ], both in older adults. However, with the same group of participants, [ 108 ] did not observe behavioral differences in an in-scanner task of hearing in noise.…”
Section: Discussioncontrasting
confidence: 94%
“…However, with the same group of participants, [ 108 ] did not observe behavioral differences in an in-scanner task of hearing in noise. Differences between observed behavioral speech-in-noise improvements and the results of this study may reflect differences in tasks [ 68 ] used the QuickSIN [ 109 , 110 ], which consists of sentences embedded in 4-talker babble. Comparison of QuickSIN and BKB-SIN, as used in this study, show greater differences between groups of differing hearing abilities in QuickSIN as compared to BKB-SIN, a difference associated with increased contextual cues present in the BKB-SIN that lead to better recognition in individuals with greater hearing loss [ 111 ].…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Musicians outperform nonmusicians in an attentive tracking experiment ( Madsen et al., 2019 ), and musicians appear to be better aware of ambiguity in ASA ( Pelofi et al., 2017 ). Studies have even observed musical training to positively affect the ability to understand speech in noise ( Dubinsky et al., 2019 ; Parbery-Clark et al., 2009 ; Puschmann et al., 2018 ; Slater et al., 2015 ; Zendel et al., 2019 ), although there is debate regarding the robustness of the effect ( Boebinger et al., 2015 ; Madsen et al., 2019 ; Ruggles et al., 2014 ). Seeking to obtain a first estimate of NH and HI listeners’ performance in musical scene analysis tasks, we here used a task that required listeners to focus their attention on a target instrument playing a short tone sequence and to separate the contributions of the target and masker signals even for low target levels.…”
Section: Perceptual Underpinnings Of Scene Analysismentioning
confidence: 99%
“…These enhancements are associated with both functional and structural differences in the brains of musicians compared to non-musicians (Kraus and Chandrasekaran, 2010;Herholz and Zatorre, 2012). Longitudinal studies have confirmed that at least some of these advantages are due to music training and not pre-existing auditory advantages (Fujioka et al, 2006;Lappe et al, 2008Lappe et al, , 2011Tierney et al, 2015;Dubinsky et al, 2019;Fleming et al, 2019;Zendel et al, 2019). One commonality between both the cross-sectional and longitudinal research is that musicians and those that are given music training as part of research are trained formally.…”
Section: Introduction Musical Training and Auditory Processingmentioning
confidence: 99%